Electroacupuncture for relieving itching in atopic eczema: study protocol for a multicenter, randomized, sham-controlled trial - Wang, Si-han; Liang, Rui-long; Yang, Han; Cai, Xiao-ce; Wang, Jiao; Sun, Xiao-ying; Chen, Jia-le; Wang, Chun-xiao; Jiang, Wen-cheng; Li, Xin (Frontiers in Medicine, 2023)
Background: Atopic eczema (AE) is a common allergic skin disease that affects approximately 15%-30% of dermatological outpatients. Atopic eczema (AE) is a common atopic inflammatory skin disease affecting 2.1-4.9% of the population in different countries. Pruritus, one of the most painfulburdensome symptoms, is often underestimated forin terms of the problems that it can cause, creating a vicious loop of itching, scratching, and lichenification.Therefore, further research into practical and safe treatments that relieve itchy symptoms and enhance skin protection is key to overcoming AE. Acupuncture, with or without electrical stimulation, is one of the most commonly used therapeutic measures to treat AE. This trial aimed to objectively evaluate the efficacy and safety of the electroacupuncture (EA) antipruritic technique in AE pruritus andclinical efficacy and safety of the electroacupuncture (EA) antipruritic technique in AE pruritus and to obtain high-level clinical evidence for the popularization and application of the EA forof AE.This is a multicenter, single-blinded, randomized controlled trial is planned to transpire from April 15, 2023, to June 30, 2025. We will recruitA total of 132 participants (44 per group) with AE (44 per group) will be recruited. Participants will be randomly assigned randomly to three equal-sized groups: electroacupuncture (EA), sham electroacupuncture (SEA), and sham acupuncture (SAC). Treatment will be administered three times a week during the two-week intervention phase. The primary outcome measure is the Visual Analog Scale, (VAS) with a numeric rating scale to evaluate pruritus. Secondary outcome measures include the Eczema Area and Severity Index (EASI) and Dermatology Life Quality Index (DLQI). Other outcome measures include physical examination, serum IgE, and safety evaluation. The number, nature, and severity of adverse events will be carefully recorded.